The Business Cycle Synchronisation In East Asia - Lee, Hooi Yean (2007)
This study examines the business cycle synchronisation in East Asia as satisfying one of the preconditions for forming an Optimum Currency Area (OCA). We extend the existing literature by improving the methodology of assessing the business cycle synchronisation in evaluating the suitability of a common currency area for East Asia employing the Bayesian State-Space Based model. This model allows us to decompose aggregate shocks into country-specific, regional and world common business cycles. The importance of studying all three different shocks in one model is that studying a subset of countries can lead one to believe that observed co-movement is particular to that subset of countries when it in fact is common to a much larger group of countries. Understanding the sources of international economic fluctuations is important for making policy decisions. For example, if a country exhibits a large value of the share accounted by the region common factor, then its business cycle movement is largely synchronised to the region, indicating that a regional common monetary policy is more effective to respond to the disturbances. As a benchmark of comparison, the business cycle synchronisation in the European Union (EU) and the North American countries are also examined. The empirical results suggest that the cost of renouncing individual currencies to advance into a currency union in East Asia could be significant as the output variation explained by country-specific factors is significant. It is worth noting that while we do not find evidence of an East Asian cycle, no evidence of an EU cycle is found either. This study also examines the endogeneity of OCA criteria. Theoretically, the effect of increased trade integration (after the elimination of exchange fluctuations among the countries in the region) on the business cycle synchronisation is ambiguous. We assess the dynamic relationships between trade, finance, specialisation and business cycle synchronisation for East Asia using the Generalised Method of Moments (GMM) approach. The dynamic panel approach improves on previous efforts to examine the business cycle synchronisation – trade link using panel procedures, which control for the potential endogeneity of all explanatory variables. The overall effect of trade on business cycles synchronisation is found to be positive, implying that increased trade leads to more synchronised business cycles. As such, policy makers may have little to worry about the region being unsynchronised in their business cycles as the business cycles will become more synchronised after the monetary union is formed.